Estimation of Insulin Resistance in Mexican Adults by the [13C]Glucose Breath Test Corrected for Endogenous Total CO2 Production - Erika Ibarra-Pastrana; Maria del Carmen Candia Plata; Gerardo Alvarez; Mauro E. Valencia (International Journal of Endocrinology)
Objective. To evaluate the efficacy of the [13C]glucose breath test for measuring insulin resistance in Mexican adults with different glycemic states. Research Design and Methods. Fifty-eight adults underwent a [13C]glucose breath test with simultaneous measurement of total CO2 production by indirect calorimetry, at baseline and 90 minutes after the ingestion of 15 g of dextrose and 25 mg of [13C]glucose. HOMA was used as a marker of insulin resistance. Results. We found an inverse correlation between HOMA and the breath test δ13CO2 (‰), r=-0.41 (P=0.001). After adjusting for total CO2 production, correlations between HOMA and fasting glucose were less strong but remained significant. An ROC curve was constructed using δ13CO2 (‰) and HOMA values; the cut-off point was 9.99‰ δ13CO2, corresponding to a sensitivity of 80.0 (95% CI: 51.9, 95.7) and a specificity of 67.4 (95% CI: 51.5, 80.9). Conclusions. The [13C]glucose breath test is a simple noninvasive procedure but was not sufficiently robust for an accurate diagnosis of insulin resistance. Our findings suggest that the test might be helpful in identifying individuals who are not IR, which in turn may contribute to improved diabetes prevention.